The Resilience of the Vulnerable Minority English Education Sector During the COVID-19 Pandemic - Advisory Board on English Education (2023)
This brief describes the vulnerabilities experienced in Québec’s English education sector, specifically in elementary and secondary schools and adult education and vocational training centres. The brief’s findings and recommendations are derived from a review of the research and from a survey conducted by ABEE. This survey (see Appendix 1) focused on the six vulnerable areas identified in the CSE report: mental health and well-being; teaching, learning and evaluation; professional development and training; governance and administration; education funding and resources; access and equity. The survey was made available in both French and English and sent to English sector teachers, administrators, parents and students. A detailed analysis of its findings is available in this brief's Research, Findings and Analysis section.

Prioritizing Student Diversity in Québec’s Education System - Advisory Board on English Education (2021)
In previous briefs to the Minister, the Advisory Board on English Education (ABEE) has given advice on inclusion in the classroom and on Indigenous education, so this brief will not address these two issues directly. It will, instead, consider the impact of discrimination and the promotion of inclusion in the school environment, the curriculum, student achievement, and teacher education. Much of the research we have identified relates to racism, and there are certainly issues specific to racist behaviour, but we recognize that the mindset that causes racist behaviour often causes discrimination against “others” of all sorts and that the remediating strategies are often similar.

Supporting English Schools in Quebec Through the Pandemic - Advisory Board on English Education (2020)
The Advisory Board on English Education (ABEE) wrote to the Minister in June, 2020 regarding the return to school. Because little has changed since then among the concerns it raised, we urge the Minister to refer back to that document, included with this letter for your convenience. In September, ABEE met virtually to assess the situation in English-language schools and centres now that they are in operation after a six-month hiatus. In the words of one member, there were “different perspectives from different people with different responsibilities but all focused on how to play our part to make this work for our students, their families and our colleagues.” The discussion was wide-ranging, but several themes emerged that we respectfully share with the Minister.

Returning to School in the English Education System in Uncertain Times - Advisory Board on English Education (2020)
The sudden and widespread occurrence of COVID-19 has pointed out the great disparities across the province of Québec, such as the different situations between the cities and the regions, and also between sectors of the population within these settings. These differences have resulted in different policy decisions, such as when—or whether—to reopen schools, and we commend the Minister for applying local solutions to local situations. We hope this strategy will continue during the uncertainty that will apply to the probable second wave of the pandemic predicted for the Fall, and we welcome the possibility of different scenarios proposed in the working document on resumption of school for all in September. An unwelcome result of the rapidly changing situation and the need for quick decisions is the appearance of hasty, spontaneous decisions that are not conveyed appropriately to the educational partners who must respond to them. Policy -makers can react quickly. Systems can not. Announcing a policy then modifying or reversing it causes stress and confusion, especially when those who must implement the policy—including principals and teachers—feel excluded from the process.

Response to the Consultation on the Proposed Ethics and Religious Culture Program - Advisory Board on English Education (2020)
The mandate of the Advisory Board on English Education (ABEE) is “to advise the Minister of Education and Higher Education on all matters affecting the educational services offered in English elementary and secondary schools and adult and vocational education centres.” For this reason, we are obliged to offer this contribution to the consultation on replacing the Ethics and Religious Culture (ERC) program, although we are frustrated that the short time allowed for consultation does not allow us to do a careful study of pertinent research and to consult with the milieu to have a fuller understanding of how this course is offered and received in the schools. Curriculum decisions, just as pedagogical decisions, should be based on conclusions from robust research. We question the value of the questions in the on-line survey: it might have been revelatory to have asked respondents to estimate their knowledge of the content and pedagogy of the existing ERC program to assess the pertinence of their opinions. Although the program occupies a small part of the overall elementary and secondary school curriculum, it is a critical program in the development of our future citizens and one that merits thoughtful consideration. Nevertheless, we also hope that the Minister will consider carefully the submissions made to him and that the proposal does not represent a fait accompli. It is clear that the relegation of the study of different religions to one reference in the eight themes of the proposed program represents the government’s intent to further the secularization of public life. However, we question whether this will effectively educate future citizens in an increasingly diverse and multi-faceted society. In the time available, we can only raise the question, but there are pedagogical and practical issues that we believe need to be considered and that we will elaborate.

Bill 40 and the English Education System in Québec - Advisory Board on English Education (2019)
In preparing this brief, the Advisory Board on English Education (ABEE) has explored the research literature on models of governance in education and listened very carefully to the reactions of schools and the wider community to Bill 40. The brief questions the relevance of the reform by asking: What problem is it trying to solve? Currently, English-language schools have an excellent success rate on provincial, national and international measures of achievement and focus on providing students with the means and options to do even better. ABEE appreciates that a form of suffrage for English boards has been maintained but feels that it falls short of the English-speaking community’s expressed expectations of universality. ABEE, along with others, has long urged the government to reform the electoral process with a view to improving voter participation. We believe that with modifications to the process, elections can be cost effective and encourage increased participation. The Board further believes that the present system of election by universal suffrage every four years has served the English-speaking community well and that any failures in governance should be dealt with on a case-by-case basis. ABEE welcomes the Bill’s intent to provide mandatory training for service centre board members and school governing board members.

Plus ça change, plus c'est pareil : Revisiting the 1992 Task Force Report on English Education in Québec - Advisory Board on English Education (2018)

Indigenous Education : Walking on Both Sides of the River - Advisory Board on English Education (2017)
Worldwide research has identified low school achievement levels among students from Indigenous cultures and there is a gradual movement to improve their situation. The Truth and Reconciliation Commission (TRC) of the Canadian government has provided the impetus for the provinces to examine their practices and the Advisory Board on English Education (ABEE) congratulates the Minister of Education, Recreation and Sports for joining this initiative. The research literature and the media have identified a broad range of issues affecting the success of Indigenous children in schools. Some of these issues, such as the remoteness and inaccessibility of the communities, poverty, the scarcity and high cost of food, poor housing, and infrastructure problems, are outside the scope of educational solutions, although they combine to have a profound effect on educational outcomes. Social and medical services must be called upon to improve the circumstances that contribute to the educational success of Indigenous students, and we hope this will be facilitated in Québec by the provincial government’s Aboriginal Social Development Action Plan. Yet education is fundamental to any potential solution to Indigenous concerns and problems, and any changes to the situation of the 100 000 Indigenous people of Québec must start with the younger generation. Many of the issues affecting the students and their success or failure in school can be addressed by the school system and this brief will identify some of them. In no way is this brief a prescription to “cure problems” in the Indigenous school system, so it does not contain recommendations, unlike most ABEE briefs. Rather, we will identify some of the issues that might contribute to the discussion of Indigenous education in Québec. We hope that some of the observations and recommendations we have made in earlier briefs regarding the Anglophone school system will be useful additions to the conversation, even though our perspective is influenced by differences between cultures and long-standing problems within Indigenous school systems.

Keeping the Door Open for Young English-speaking Adults in Québec : Language Learning in English Schools and Centres - Advisory Board on English Education (2016)
During a committee hearing in April 2015, Premier Philippe Couillard responded to a question from Mr. David Birnbaum (MNA for D’Arcy-McGee) about “what our government has done and plans to do to ensure that young anglophone Quebecers are full and valued participants in building our future,” by saying that he wanted to hear from the English-speaking community. About the same time, then-Minister of Education Bolduc asked the Advisory Board on English Education (ABEE) to advise him on how to encourage English-speaking youth to remain in Québec. In May 2016, Premier Couillard identified the English educational sector as a model for the system as a whole, and the Board proposed some reasons for this success in its most recent brief. It should be noted that students in the English sector achieve this success while receiving instruction in two languages from kindergarten onward. The ability to function in two languages is recognized as a crucial socio-economic skill for young Anglophones, and has an impact on their decision whether or not to stay in Québec. How can the education system contribute to developing this skill? This brief is respectfully presented to the Minister of Education with recommendations that respond to this question.

"We Are Accountable to the Students" : Success and Retention in English-language Schools - Advisory Board on English Education (2015)
In February 2015, the Advisory Board on English Education was given a mandate from the former Minister of Education to examine the successes experienced in the English-language schools of the province, identify the conditions present in the schools that contribute to these successes, and suggest how these conditions might be transferred throughout the education network in Québec. The Board has carried out this mandate, believing that the issues are relevant and important enough to be addressed, but aware that many of the factors identified in this brief are not novel and may be recognizable to anyone familiar with good educational practice.

Québec Schools On Line : Opportunities for English-Language Education - Advisory Commitee for English-Speaking Quebecers (2014)
In 1996, The Advisory Board on English Education (ABEE) prepared a brief on the integration of technology into English language schools, noting the particular needs of these schools, especially in rural areas, and making recommendations on accessibility, teacher support, and school organization, among other issues. The current Board notes how much—and how quickly— the technology has changed since 1996 but, based on its strongly held belief that technology is subordinate to pedagogy, it endorses in principle the content of this earlier document. Yet the technology available for classroom use has changed, it has done so at a speed unimaginable in 1996, and done so qualitatively as well as quantitatively, making it imperative that a broad-based discussion of technology in teaching take place as part of our changing understanding of teaching and learning. In addition, the problems in English language schools and centres caused by demographics, distance and dispersion have become more acute and more in need of ingenious solutions so that their graduates are prepared for the 21st century, and potential solutions to these problems through Information and Communications Technologies (ICT) merit discussion. This brief addresses both the general issues and those pertinent to the English education system in Québec, and includes a set of recommendations to help in the formulation of MELS orientations.

One Size Does Not Fit All: Distinct Solutions for Distinct Needs - Advisory Board on English Education (2013)
In this report to the Minister, the Advisory Board on English Education is taking the opportunity to review the themes and concerns identified in earlier correspondence, reports and briefs that continue to describe English education in Québec accurately, and to update them with current examples of both concerns and successes. We emphasize that there is no intention to promote one system over another, nor to assign fault. We believe that many of the inherent difficulties faced by English school boards, schools and centres could be mitigated if MELS were to take better account of the differences between the two sectors in its policies and their implementation. It is hoped that a description of the distinctiveness of the English sector and how it functions differently from the French sector will provide some insight as to how the English system is frequently constrained by many of the Ministry’s policies, especially in their application, and indicate the need for flexibility in implementing policy. This will ensure that the English education system can continue to prepare its graduates to participate fully in the life of Québec society.

Briefs Submitted to the Minister of Education, Recreation and Sports : 2012 - Advisory Board on English Education (2012)

Briefs Submitted to the Minister of Education, Recreation and Sports : 2011 - Advisory Board on English Education (2011)

Fostering Student Success in Québec's English School : Implications for Policy and Practice - Advisory Board on English Education (2011)

[Letter to the Minister Concerning Issues of Inclusion and Integration in the Classroom] - Advisory Board on English Education (2010)

Educating Today's Québec Anglophone - Advisory Board on English Education (2010)

High-quality Teachers and Administrators for English-language Schools in Québec : Preparation, Induction and Support - Advisory Board on English Education (2009)
The Advisory Board on English Education begins by commending the teachers and principals of the English-language schools of the province for the crucial work they do in educating the future citizens of Québec, Canada, and the world. Education has always been an important preoccupation of English-speaking Quebeckers. Graduates of English-language schools have contributed greatly to the institutions of the province, and the schoolhouse has traditionally provided a focal point for rural populations of the community. Worldwide, there is a recognition that education must change to accommodate the needs of twenty-first century graduates, and that therefore the curriculum and teachers must also change. Many countries have developed initiatives that aim to prepare, support, and retain teachers more effectively than in the past, and to encourage young people to become teachers, especially in disciplines such as science and mathematics, seen as necessary for living in contemporary society. Our goal in this brief is to respond to the preoccupation that the English-language schools of Québec need even more good teachers and principals who, in turn, need more appropriate preparation and more support so that they do not leave the profession but continue to develop within it.

Response to the Minister of Education Regarding School Board Governance - Advisory Board on English Education (2008)

Special Education : Issues of Inclusion and Integration in the Classroom - Advisory Board on English Education (2006)

Decentralization, Regionalization and Adaptation (DRA) : Jamais deux sans trois - Advisory Board on English Education (2006)
The issue of regionalization—not just in education but also across the entire spectrum of government policy making and service delivery—is not a new one. In recent years two successive governments have made discussion of regionalization and decentralization a priority with a view to making government policies and services more responsive to local and regional needs.

The Transitions Beyond Secondary : Report to the Minister of Education of Québec - Advisory Board on English Education (2004)

Profile of the Teacher as Keystone in Secondary Reform Implementation : Report to the Minister of Education - Advisory Board on English Education (2003)

Policy Environment for the Implementation of School Reform - Advisory Board on English Education (2001)

English Schools in Transition : Building Collaborative Leadership - Advisory Board on English Education (2000)

Culture and English Schools in Play - Advisory Board on English Education (1999)
In this 1999 report to the Minister of Education, the Advisory Board on English Education examines Québec Schools on Course, the educational policy statement published by the Ministère de l’Éducation du Québec (MEQ) which calls for improvement of the cultural content of the curriculum.

A Challenge for English School Boards : Regionalization and Vocational Education - Advisory Board on English Education (1998)

Evaluation of Learning in the English Schools of Québec - Advisory Board on English Education (1997)
This report reviews the existing regulatory guidelines for evaluation of learning. Within that context the Advisory Board reports on the attitudes and perceptions of students, parents and educators, based on an extensive survey of their views. The report concludes with a set of recommendations which can guide further discussion on this vital topic. The Evaluation of Learning - Student, Parent, and Educator Questionnaires. Quantitative Analysis of Results - Final Report follows the recommendations, along with the full text of the Educator Questionnaire.

The Integration of the New Information and Communication Techologies in the English Schools of Québec - Advisory Board on English Education (1997)
At a time when the reform of education is under way and there is mounting pressure to integrate the new information and communication technologies in schools, the Advisory Board on English Education has tried to identify some of the opportunities for and barriers to an effective implementation of technological developments, in order to allow English schools to take full advantage of the new technologies for the enhancement of learning. To this end we have focused on the four key elements of the educational process most conducive to change: the role of the teacher, student learning, school organization and the need to expand the present technological network throughout the school system.

Language Learning in the English Schools of Quebec : A Biliteracy Imperative - Advisory Board on English Education (1995)
The school board reorganization, which sooner or later is bound to come about, will force major adjustments on the delivery of English education. The forming of a true English school network through the fusion of the existing Catholic and Protestant structures will provide both an opportunity to strengthen and rationalize the English school system and a challenge to get it right. By getting it right is meant finding an educational mission to which all the constituencies of the English-speaking community and the schools which serve it can respond.

The Reorganization of School Boards Along Linguistic Lines : Bill 107 : An English Perspective - Advisory Board on English Education (1994)
At the Advisory Board's first meeting of the 1993-1994 school year, a strong consensus emerged that the issue of school board reorganization should be addressed and that the English-speaking community should be consulted as to its views on language based boards and informed about the legislation governing their implementation.

Report to the Minister of Education : Textbooks and Teaching Materials - Advisory Board on English Education (1993)
The Advisory Board on English Education was asked to study the issues of the availability, accessibility and suitability of the textbooks and teaching materials provided and produced for the English language public school system in conformity with the objectives and programs of the Regime pedagogique. When the Advisory Board undertook this exercise, the most striking feature of the textbook "problem", as expressed in anecdotal form by all those consulted, was the uneveness of accessibility and a wide spread confusion about what was or was not available. These two factors have contributed to a sense of insecurity in the implementing of programs and a questioning of the suitability of the textbooks and teaching materials which do come on the market.

English-Language Education in Québec : A Response to the Task Force on English Education - Advisory Board on English Education (1993)
It is the responsibility of the Minister of Education to ensure quality in the educational services provided by the education system to the population of Québec. It was with the objective of ensuring quality service to English-speaking students, that a task force on English education was mandated in September 1991 to examine four key areas of concern: the decline of the English school population, the situation of small schools, vocational education and the exodus of young English-speaking Quebecers. The English-speaking community has always been and continues to be an integral part of Québec society. It reflects the important diversity that has always been present in Québec, a diversity that offers strength and an outward-Iooking vision. English institutions not only give valuable service but also play an important role in developing leadership in the Québec community. These institutions deserve support and young anglophone Quebecers must feel that their schools are responsive and dynamic institutions which are changing with the times. English schools must provide these young people with, not only a knowledge of their past but also a vision of their future in Québec.

Task Force on English Education : Report to the Minister of Education of Quebec - Advisory Board on English Education (1992)